2017
DOI: 10.1038/srep41928
|View full text |Cite
|
Sign up to set email alerts
|

Geosmin-producing Species of Coelosphaerium (Synechococcales, Cyanobacteria) in Lake Shinji, Japan

Abstract: In Lake Shinji, Japan, periodic outbreaks of musty odour have occurred since mid-May 2007. Although the substance responsible for the odour was identified as geosmin, the odour-producing organism was unknown. We cultivated an axenic unialgal strain and determined that a species of Coelosphaerium (Synechococcales) was responsible for the production of geosmin in Lake Shinji. Our analysis was conducted using gas chromatography/mass spectrometry to determine the odorous compound. To determine the algae species, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The species of Cyanobacteria producing geosmin are diverse, belonging to several distinct taxons, namely, multicellular strains of Oscillatoriales, Nostocales and Synechococcales 10,11,23 and recently the unicellular Synechococcales Coelosphaerium sp. 13 , debunking the idea that only filamentous Cyanobacteria could produce geosmin 24,25 . Most of the knowledge on cyanobacterial producers is from freshwaters, probably due to the blooms related to odor and musty taste issues, while terrestrial, brackish and marine producers are rarely described or absent 11,15,24,25 .…”
mentioning
confidence: 99%
“…The species of Cyanobacteria producing geosmin are diverse, belonging to several distinct taxons, namely, multicellular strains of Oscillatoriales, Nostocales and Synechococcales 10,11,23 and recently the unicellular Synechococcales Coelosphaerium sp. 13 , debunking the idea that only filamentous Cyanobacteria could produce geosmin 24,25 . Most of the knowledge on cyanobacterial producers is from freshwaters, probably due to the blooms related to odor and musty taste issues, while terrestrial, brackish and marine producers are rarely described or absent 11,15,24,25 .…”
mentioning
confidence: 99%
“…Sphaerospermopsis, Cylindrospermopsis and Nodularia were investigated genera in this study which were already reported as GEO or MIB producer in previous studies (Popin et al 2016, Watson et al 2016, Zhang et al 2017, Pham et al 2020. Also, Microcystis strains were investigated with the knowledge of other coccoid cyanobacteria such as Synechococcus C.Nägeli or Coelosphaerium Nägeli as a producer (Kutovaya & Watson 2014, Godo et al 2017). On the other hand, the results are limited with the investigated strains and VOC production may vary from one strain to another (Watson et al 2016).…”
Section: Dolichospermummentioning
confidence: 99%
“…The molecular weight (MW) and isoelectric point (pI) of each predicted MaVPE protein sequence were calculated using ExPASy 5 . Multiple sequence alignment analysis of MaVPE proteins were performed using the ClustalW logarithm (Godo et al, 2017). Further processing of the alignment files was conducted in the BioEdit sequence alignment editor (version 7.1.3.0) with default parameter settings.…”
Section: In Silico and Phylogenetic Analysismentioning
confidence: 99%